(untitled) (SCIENCE TIME JOURNAL, 2026)
This study investigates the role of stylistic devices in the creation of artistic images in J.K. Rowling‘s Harry Potter and the Philosopher’s Stone and examines their interpretation in the Uzbek translation. The research aims to identify the main stylistic devices employed by the author and evaluate the effectiveness of their translation into Uzbek. The study applies comparative, descriptive, and linguostylistic methods to analyze metaphors, epithets, similes, hyperbole, irony, personification, repetition, and antithesis found in the source text and their translated equivalents. The findings reveal that stylistic devices play a crucial role in character development, atmosphere creation, and emotional expressiveness. The analysis demonstrates that most stylistic elements are successfully rendered through direct translation, stylistic substitution, and contextual adaptation. However, certain culture-specific and irony-based expressions undergo semantic modification in the translation process. The study concludes that preserving stylistic imagery and emotional impact is essential for achieving translation equivalence and maintaining the artistic value of the original text.